2022
DOI: 10.3389/fimmu.2022.958418
|View full text |Cite
|
Sign up to set email alerts
|

Charlson comorbidity index, neutrophil-to-lymphocyte ratio and undertreatment with renin-angiotensin-aldosterone system inhibitors predict in-hospital mortality of hospitalized COVID-19 patients during the omicron dominant period

Abstract: PurposeTo investigate the clinical predictors of in-hospital mortality in hospitalized patients with Coronavirus disease 2019 (COVID-19) infection during the Omicron period.MethodsAll consecutive hospitalized laboratory‐confirmed COVID-19 patients between January and May 2022 were retrospectively analyzed. All patients underwent accurate physical, laboratory, radiographic and echocardiographic examination. Primary endpoint was in-hospital mortality.Results74 consecutive COVID-19 patients (80.0 ± 12.6 yrs, 45.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 68 publications
1
18
0
Order By: Relevance
“…A CCI score ≥ 3 was prognostically associated with mortality in hospitalized COVID-19 patients [36]. Moreover, a CCI ≥ 7 and an NLR ≥ 9 were among the main prognostic indicators for in-hospital mortality in patients with COVID-19 during the Omicron period [37]. We likewise observed a correlation between the NLR and CCI in hospitalized COVID-19 patients with associated medical comorbidities.…”
Section: Discussionsupporting
confidence: 65%
“…A CCI score ≥ 3 was prognostically associated with mortality in hospitalized COVID-19 patients [36]. Moreover, a CCI ≥ 7 and an NLR ≥ 9 were among the main prognostic indicators for in-hospital mortality in patients with COVID-19 during the Omicron period [37]. We likewise observed a correlation between the NLR and CCI in hospitalized COVID-19 patients with associated medical comorbidities.…”
Section: Discussionsupporting
confidence: 65%
“…Additionally, the results highlighted that the overall burden of comorbidity assessed by the age-adjusted Charlson comorbidity index was an independent risk factor for the Ct values. It has been reported that the Charlson comorbidity index predicted poor clinical outcomes and mortality in COVID-19 patients ( 7 , 32 ). Therefore the Charlson Comorbidity index might contribute to the management of the older patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Omicron infection was associated with a lower rate of hospital admission and mortality ( 5 , 6 ). However, the elderly were more likely to be infected with Omicron due to immunosenescence and high comorbidity burden ( 7 , 8 ). The rate of severe Omicron infections were increased in the older patients and in individuals with comorbidities such as hypertension, diabetes, cardiovascular disease, and chronic respiratory disease ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…For other significant factors in model 4, they were either unstable or only partially reflected the patient's physical condition. In addition, the most frequently reported predictors of prognosis in COVID-19 patients were age, symptoms, comorbidities, and features derived from CT ( 15 , 16 , 37 40 ). A high proportion of severe cases and high mortality were observed in elderly COVID-19 patients ( 41 , 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Patients showed various symptoms, and some symptoms would also change over time, indicating that they were not appropriate or reliable indicators for all patients. Comorbidities or the relevant evaluation indicator, Charlson's Index, was associated with mortality ( 40 ). However, Charlson's Index was always concerned with long-term prognosis and could not provide a real-time view of a patient's functional state after being affected by COVID-19 like the Barthel Index.…”
Section: Discussionmentioning
confidence: 99%